(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The scientific article written by a group of authors discusses the importance of effective organization of innovative activities in construction enterprises. At the same time, suggestions and recommendations were given that construction companies face a lot of problems today, and innovative measures are needed to solve them.